Active Crossfire Between Cyanobacteria and Cyanophages in Phototrophic Mat Communities Within Hot Springs - Guajardo-Leiva, Sergio; Pedrós-Alió, Carlos; Salgado, Oscar; Pinto, Fabián; Díez, Beatriz (Frontiers in Microbiology, 2018)
Cyanophages are viruses with a wide distribution in aquatic ecosystems, that specifically infect Cyanobacteria. These viruses can be readily isolated from marine and fresh waters environments; however, their presence in cosmopolitan thermophilic phototrophic mats remains largely unknown. This study investigates the morphological diversity (TEM), taxonomic composition (metagenomics), and active infectivity (metatranscriptomics) of viral communities over a thermal gradient in hot spring phototrophic mats from Northern Patagonia (Chile). The mats were dominated (up to 53%) by cosmopolitan thermophilic filamentous true-branching cyanobacteria from the genus Mastigocladus, the associated viral community was predominantly composed of Caudovirales (70%), with most of the active infections driven by cyanophages (up to 90% of Caudovirales transcripts). Metagenomic assembly lead to the first full genome description of a T7-like Thermophilic Cyanophage recovered from a hot spring (Porcelana Hot Spring, Chile), with a temperature of 58°C (TC-CHP58). This could potentially represent a world-wide thermophilic lineage of podoviruses that infect cyanobacteria. In the hot spring, TC-CHP58 was active over a temperature gradient from 48 to 66°C, showing a high population variability represented by 1979 single nucleotide variants (SNVs). TC-CHP58 was associated to the Mastigocladus spp. by CRISPR spacers. Marked differences in metagenomic CRISPR loci number and spacers diversity, as well as SNVs, in the TC-CHP58 proto-spacers at different temperatures, reinforce the theory of co-evolution between natural virus populations and cyanobacterial hosts. Considering the importance of cyanobacteria in hot spring biogeochemical cycles, the description of this new cyanopodovirus lineage may have global implications for the functioning of these extreme ecosystems.